Financial accounting : a global approach - Gray, S. J. (Sidney J.); Needles, Belverd E. (Boston : Houghton Mifflin, 1999)
This book is about: Accounting as an information system; The measurement of financial position and performance; Special topics in financial accounting and analysis; ...
Keywords: Accounting; Economics; Accounting